The value of information in the face of new global disorder - Corrêa da Silva, Fabiano Couto (AWARI, 2022)
We analyzed how the media disseminate information based on five filters indicated by Chomsky and Herman (2003): Filter 1: Importance, ownership, and benefits orientation of the media; Filter 2: Advertising as the primary source of income; Filter 3: The supply of news to the media; Filter 4: Corrective measures as a method to discipline the media; Filter 5: Anticommunism as a control mechanism. The analysis showed that in addition to fake news, real news is manipulated and oriented to polarize ideologically, requiring an adaptation of society in building regulatory frameworks. At the same time, companies and their logarithms cannot counteract the global networks of disinformation that cross countries, continents, and languages. When there are news sources for us to access more efficiently, the convenience of following the communication channels that we have more identification with our interests can become a well-designed trap, as demonstrated by Chomsky and Herman's (2003) 5 filters. We need to distinguish the reliability of the information, and it is necessary to use some analytical skills. Many people do not understand these manipulation mechanisms; it becomes easier to believe this information and share it again, making a continuous cycle of sharing and feedback of low-quality information.